Self-efficacy and the process of gay sexual identity development among gay men in Malaysia - Carmella E. Ading; Aminuddin Ibrahim Lastar; Getrude C. Ah Gang; Mohammad Hashim Othman (inScience Press, 2021)
The development of gay identity sexual among Malaysian gay men were not discussed openly in this country. This is because the government do not approve same sex orientation lifestyle. However, gay men exist in many communities in this country and they are living freely as a citizen and work in the country like others. Malaysia is one of the countries that openly against the Lesbian, Gay, Bisexual, Transsexual and Queer (LGBTQ). Nevertheless, they continue to develop their sexual identity as a part of their lives which at the same time causes a great distress in them. Thus, their decision to identify themselves as gays takes huge courage and effort. These courage and effort were found not only just intricately, since it involves emotional and social support from their family, friends and communities. It is also believed that this social support might help gay men to develop their self-efficacy as well. Therefore, it is in the interest of the researchers to explore about self-efficacy by looking at emotional and social support they received and its relation to the development of sexual identity among the gay men who lives in Malaysia. In this qualitative research, semi structured questions were developed to explore sexual identity development among the gay men. Six (6) respondents who have identified themselves as gay, aged between 21- 44 years old, from different walk of life were interviewed. Data were analysed using thematic analysis. Our study has found that emotional and social support, are the important factors that contribute to their self-efficacy and help them in developing their sexual identity.